EDUKASI FISIKA MELALUI FILM FIKSI ILMIAH DALAM KEGIATAN PENGABDIAN KEPADA MASYARAKAT: PHYSICS EDUCATION THROUGH SCIENCE FICTION FILM IN COMMUNITY SERVICE ACTIVITIES - Alfikri Dwi Mauluda; Naily Ulya; Devi Nurhanivah (LPPM Universitas Abdurrab, 2025)
Technological advances in the era of globalization cannot be separated from the basic concepts of physics, especially in the fields of electricity and magnetism. However, the reality in the field shows that many students have difficulty in understanding these concepts because learning is still theoretical and less interesting. Conventional teaching methods often make it difficult for students to connect theory with application in everyday life. Therefore, this study aims to improve students' physics literacy by utilizing science fiction film media as a more interactive and interesting learning tool. This Community Service (PkM) activity was carried out at SMA Negeri 2 Padalarang involving 63 grade XII science students. This program is designed with an approach that includes providing systematic material, discussion sessions that build conceptual understanding, and demonstrations through science fiction films that are relevant to the topic of electricity and magnetism. The use of films in learning aims to provide a more concrete visual experience so that students can more easily understand the application of physics concepts in various modern technological phenomena. This science fiction film-based approach is effective in increasing students' interest in physics, as shown through active participation in discussions and positive responses through evaluation questionnaires. This is also proven by the results of data analysis showing an increase in the average pretest score of 35.71 to 57.94 in the posttest, with an overall N-Gain value of 0.35 which is included in the moderate category. Thus, the use of science fiction film media can be an innovative alternative in learning physics that is more enjoyable and effective.